Relationship between pure-tone audiogram findings and speech perception among older Japanese persons. (1st February 2018) - Maeda, Yukihide; Takao, Soshi; Sugaya, Akiko; Kataoka, Yuko; Kariya, Shin; Tanaka, Satomi; Nagayasu, Rie; Nakagawa, Atsuko; Nishizaki, Kazunori
Abstract: Objective: To clarify how the pure-tone threshold (PTT) on the PTA predicts speech perception (SP) in elderly Japanese persons. Methods: Data on PTT and SP were cross-sectionally analyzed in Japanese persons (656 ears in 353 patients, aged ≥65 years). Correlations of SP and average PTT in all tested frequencies were evaluated by Pearson's correlation coefficient and simple linear regression. After adjusting for sex, laterality of ears, and age, the relationship of average and frequency-specific PTT with impaired SP ≤50% was estimated by logistic regression models. Results: SP correlated well ( r  = −0.699) with the average PTT of all tested frequencies. On the other hand, the correlation between patient age and SP was weak, especially among ≤85-year-old persons ( r  = −0.092). Linear regression showed that the average PTT corresponding to SP of 50% was 76.4 dB nHL. Odds ratios for impaired SP were highest for PTT at 2000 Hz. Odds ratios were higher for middle (500, 1000, 2000 Hz) and high frequencies (4000, 8000 Hz) than low frequencies (125, 250 Hz). Conclusion: The PTT on the pure-tone audiogram (PTA) is a good predictor of SP by speech audiometry among older persons, which could provide clinically important information for hearing aid fitting and cochlear implantation.